Design of Ultra Wideband RF IC for Medical Imaging Applications - Bidhendi , Hossein Kassiri (My University, 2010)
Being the second most important cause of death in women, breast cancer attracted great interest from many research groups in different fields developing techniques to prevent, detect or cure it. Due to the fact that this disease can be treated if it is detected in early stages, many projects in this field have focused on early breast cancer detection. Modern imaging technologies have helped in the detection of this cancer but they still have high false positive or negative rates indicating a great need for more research in early breast cancer detection.
In 2002 the Federal Communication Commission allowed usage of 3.1 - 10.6 GHz frequency range for short-range medical and personal applications, and this has stimulated much research on one of the most interesting technologies for medical imaging. With the aid of advances in complementary metal-oxide-semiconductor technology as well as wireless communications, this imaging technology has steadily grow, and now, it has it has many attractive characteristics that makes it a perfect substitute for conventional imaging systems.
This thesis reports on the design of some key circuits for an ultra-wideband transceiver architecture that can be used for medical imaging and especially for breast cancer detection. In this work, we concentrated on the receiver and two of its major blocks, namely, a low noise amplifier and a mixer are designed, simulated, fabricated and tested. Both of these circuits are designed in 0 .13 μm technology and Cadence tools are used for simulation and layout.
First, a low noise amplifier is designed based on a common-source configuration with inductive degeneration and a third order Chebyshev input matching network. Using precise zero-pole analysis, two inductors have been added to the main architecture of amplifier to improve its gain bandwidth product. The designed circuit shows a very good performance in terms of all of design parameters. Voltage gain with a peak value of 18.6 dB and very acceptable flatness is achieved. Also the noise figure of this circuit had an average of 4.7dB and a minimum value of 3.3dB. Input and output impedance matching shows very satisfying performance for the whole range of 3.1 to 10.6 GHz. Moreover, linearity of the circuit shows a very good performance compared with other works with IIP3 of -0.996 dBm. Finally, all of these specifications are achieved while consuming only 4.01 mW and occupying 1.3 mm2 of chip area.
Second, an ultra-wideband mixer is designed to work as a multiplier in this configuration, and to perform a critical function in correlation block. The mixer is designed for both super- and sub-threshold modes of MOSFET operation, and in both modes, it shows very acceptable performance. While super-threshold mixer shows much better characteristics in terms of gain, noise and linearity, the very low power consumption of sub-threshold circuit along with its reasonable performance in terms of gain, noise and linearity makes both circuits excellent designs for niche applications. Excellent conversion gain of 22.54dB is achieved for super-threshold circuit together with minimum noise figure of 7.4 dB and IIP3 of 2.67 dBm, while consuming 6.67 mW and having excellent input impedance matching all over the bandwidth. On the other hand, the sub-threshold circuit dissipates only 623 μW, with 13.44 dB of conversion gain and minimum noise figure of 7.67 and IIP3 of -7.47 dBm. This circuit has excellent input matching all over the UWB frequency range.
Keywords: breast cancer; modern imaging technology